Increasing Pre-service Special Education Teacher Skills on Performance Feedback - Owens, Tosha L.; Hudson, Melissa E.; Voytecki, Karen S. (Journal of the American Academy of Special Education Professionals, 2022)
Special educators are often placed in a collaborative leadership role, supporting others in implementing appropriate educational supports for students with disabilities across the educational environment. Furthermore, special educators are often seen as agents of change, often coaching peer-teachers to ensure best practices are being used to gain the most progress. This study investigated the impact of a training package focused on teaching performance feedback skills on the number of performance feedback statements made by 24 pre-service special education teacher majors during debrief meetings immediately following simulated teaching experiences. Results indicated that, prior to the intervention, participants gave their peers two and one half times more positive feedback than constructive and made themselves the focus of constructive feedback twice as often as their peers. Following the intervention, the number of constructive performance feedback statements given to peers increased while the number of positive performance feedback statements remained stable.